Comparison of the rates of stroke and acute coronary events in northern France. (September 2018) - Cottel, Dominique; Montaye, Michèle; Marécaux, Nadine; Amouyel, Philippe; Dallongeville, Jean; Meirhaeghe, Aline
Background: Although stroke and acute coronary events share several risk factors, few studies have compared population-level epidemiological surveillance indicators of the two diseases in the same age range and in the same geographical area. Design: The objective of the present study was to compare the rate of acute coronary events with that of stroke among inhabitants aged from 35–74 years in Northern France (Lille). Methods: All incident and recurrent acute coronary events and stroke events occurring in men and women over 2008–2014 were recorded using two population-based registries with several overlapping sources of case ascertainment for hospitalised/non-hospitalised and fatal/non-fatal events. Log-linear Poisson regression models were used to compare the event and mortality rates. Results: The results showed that the incident rates of acute coronary event and stroke were similar except under 60 years. In this group (35–59 years), the incident rate of acute coronary events was 1.6-fold higher than that of stroke. In contrast, the attack (incident and recurrent) rates were higher for acute coronary events than for stroke (1.5-fold; p  < 0.0001) – especially in men (1.8-fold; p  < 0.0001). The mortality rate was 2.2-fold higher for acute coronary events than for stroke, independent of sex and age group ( p  < 0.0001), as was the case-fatality rate (1.5-fold, p  < 0.0001). Conclusion: In Lille, the overall acute coronary event rate was higher than the stroke rate – especially among men, due to a higher risk of incident acute coronary event under the age of 65 and a higher risk of recurrent acute coronary event in the 65–74 year-old age range. Further efforts should be devoted to primary and secondary prevention strategies after acute coronary events.